Fostering an ecological shift through effective environmental education - Kochetkova, Tatjana (IGI Global, 2024)
In the face of our planet's escalating environmental crisis and climate change, humanity stands at a crossroads, urgently requiring a transformative response. The task of averting environmental destruction necessitates not only a shift in our economy and technology but, more fundamentally, a profound cultural transformation. This imperative transformation involves a collective move from the self-centered "Ego" to an ecologically conscious "Eco." To unravel the complexities of this metamorphosis, scholars are turning to the potent tool of environmental education, recognized for its capacity to foster personal and social growth while promoting environmental conservation. Enter Fostering an Ecological Shift Through Effective Environmental Education, a groundbreaking exploration into the transformative power of education in the pursuit of sustainable change.As readers embark on this scholarly journey, the book reveals the profound psychological connection to nature achievable through environmental education. It scrutinizes the connection between heightened nature awareness and the adoption of sustainable practices, providing valuable insights for educators at various levels. The chapters traverse diverse topics, from the historical roots of environmental education to the role of indigenous knowledge, yoga, and eco-spirituality within nature education. The book's comprehensive approach extends to eco-therapy, forest school programs, and the influence of parents in environmental education. By scrutinizing case studies and global movements, this work illuminates the achievements and challenges of environmental education on both national and global scales.